PROSES MANAJEMEN EDITORIAL DI GRAMATA PUBLISHING - Meilina Ika Kurniawati; Benget Simamora (Politeknik Negeri Media Kreatif, 2014)
This research aims to clarify and expose the causes of the less effective the editorial management process in Gramata Publishing. The descriptive method was used to describe the process of editorial management in Publishing studies based on data Gramata library and observations directly at Gramata Publishing. The results showed an overview the process of publishing a book on Self- publishing is not raw Gramata. Sometimes in the process of management there is a change for the sake of efficiency.